Information Fusion Model of Age‑Appropriate Home Environment Design in Pervasive Computing Environment - Zhang, Yun; Musdi, Shanat; Li, Ya (Springer, 2023)
In order to make intelligent products better serve the daily life of the elderly, an information fusion model of age-appropriate home environment design under pervasive computing environment is proposed. Construct the human-computer interaction model of smart home system; Taking the basic framework of traditional behavior prediction system as the starting point, the elderly smart home behavior prediction system is constructed from four levels: acquisition layer, interaction layer, transport layer and service layer. On this basis, the “moderate” intelligent principle and design strategy of smart home products for the aged are put forward, and the design practice and design evaluation of related products are carried out. The results show that the average score of the overall design of intelligent medicine cabinet is 8.75 and 8, respectively. The average score of ten experts is 8.2875, which indicates the experts’ armation of the product design scheme to a certain extent. Among them, the average score of functional practicality and interface visibility is 9.1 and 8.5 respectively, which indicates that the design of these two levels is not only feasible but also has certain reference value. Secondly, the average score of innovative function, aesthetic beauty of form, safety of operation and interactivity of interface all reached the expected standard, indicating that it meets the use needs of the elderly and conforms to the construction of the system. However, the average score of color collocation and operation logic is lower than 8 points, indicating that compared with other factors, these two levels need further improvement and improvement. Conclusion: The design method of intelligent products for the aged proposed in this study provides a new solution for home care for the elderly, and makes intelligent products provide high-quality service and guarantee for the happy life of the elderly to the greatest extent.